Potential reliability and validity of a modified version of the Unified Parkinson's Disease Rating Scale that could be administered remotely - Abdolahi, Amir; Scoglio, Nicholas; Killoran, Annie; Dorsey, E. Ray; Biglan, Kevin M. (Parkinsonism & related disorders, 2013)
By permitting remote assessments of patients and research participants, telemedicine has the potential to reshape clinical care and clinical trials for Parkinson disease. While the majority of the motor Unified Parkinson's Disease Rating Scale (UPDRS) items can be conducted visually, rigidity and retropulsion pull testing require hands-on assessment by the rater and are less feasible to perform remotely in patients' homes. In a secondary data analysis of the Comparison of the Agonist pramipexole vs. Levodopa on Motor complications in Parkinson's Disease (CALM-PD) study, a randomized clinical trial, we assessed the cross-sectional (baseline and 2 years) and longitudinal (change from baseline to 2 years) reliability of a modified motor UPDRS (removing rigidity and retropulsion items) compared to the standard motor UPDRS (all items) using intraclass correlation coefficients (ICC), stratified by treatment group. Internal consistency of the modified UPDRS (mUPDRS) was measured using Cronbach's alpha, and concurrent validity was assessed using Pearson's correlation coefficient (r) between the standard motor UPDRS and mUPDRS. The mUPDRS versus standard motor UPDRS is cross-sectionally (ICC ≥ 0.92) and longitudinally (ICC ≥ 0.92) reliable for both treatment groups. High internal consistencies were also observed (α ≥ 0.96). The mUPDRS had high concurrent validity with the standard UPDRS at both time points and longitudinally (r ≥ 0.93, p < 0.0001). A modified version of the motor UPDRS without rigidity and retropulsion pull testing is reliable and valid and may lay the foundation for its use in remote assessments of patients and research participants.